Can's Tago mago : permission to dream - Warner, Alan (33 1/3., 2014)
"'An officially approved account of one of the most influential and powerful albums of the 1970s, this brilliant addition to the 33 1/3 series by Scottish novelist Alan Warner will explore in detail the conception, recording and release of the album Tago Mago by Can"--Provided by publisher